1981
DOI: 10.7883/yoken1952.34.293
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Rotavirus Infection in the Tropics

Abstract: SUMMARY:The age distribution of rotavirus antibody in the serum of inhabi tants of Laos and Indonesia was studied by the neutralization test using antigenically related calf rotavirus (NCDV) as a substitute for non-cultivable human rotavirus. The results revealed that both the rate of antibody-positives and the modal titers of antibody distribution by each age group in these countries were higher than those in respective age groups of Japanese, which suggest higher endemicity of rotavirus infection in these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…In the present study a 54.2% infection rate was reported among children aged 0–1 year. This finding is in agreement with previous studies done in Jakarta and Medan, Indonesia [18], which showed a 53% rate of rotavirus in diarrheic patients who were 1 year of age or less. Another study in Bahrain showed that rotavirus was detected most frequently among the age group of 6–11 months [25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study a 54.2% infection rate was reported among children aged 0–1 year. This finding is in agreement with previous studies done in Jakarta and Medan, Indonesia [18], which showed a 53% rate of rotavirus in diarrheic patients who were 1 year of age or less. Another study in Bahrain showed that rotavirus was detected most frequently among the age group of 6–11 months [25].…”
Section: Discussionsupporting
confidence: 93%
“…In developing countries such as Indonesia, few studies to determine the incidence of viral‐related acute gastroenteritis have been reported [16,18]. Knowledge of the etiology of acute diarrhea associated mainly with viral‐related pathogens is relevant for planning diarrhea disease control strategies in Indonesia, which will be useful for future vaccine development in the region.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study a 54.2% infection rate was reported among children aged 0^1 year. This ¢nding is in agreement with previous studies done in Jakarta and Medan, Indonesia [18], which showed a 53% rate of rotavirus in diarrheic patients who were 1 year of age or less. Another study in Bahrain showed that rotavirus was detected most frequently among the age group of 6^11 months [25].…”
Section: Discussionsupporting
confidence: 93%
“…In developing countries such as Indonesia, few studies to determine the incidence of viral-related acute gastroenteritis have been reported [16,18]. Knowledge of the etiology of acute diarrhea associated mainly with viral-related pathogens is relevant for planning diarrhea disease control strategies in Indonesia, which will be useful for future vaccine development in the region.…”
Section: Introductionmentioning
confidence: 99%
“…In one study carried out in South Africa (7) the rate of rotavirus detection in infantile gastroenteritis was 6%190/0. A survey from the tropics (20) showed a rate of rotavirus detection of 45%. In temperate zones the number of rotavirus gastroenteritis cases peaks sharply in the winter season, while apart from reports of some peaking in the dry seasons, outbreaks seem to be more evenly distributed throughout the year in the tropics.…”
mentioning
confidence: 99%